PENGETAHUAN KELUARGA DALAM PENGASUHAN DAN TUMBUH KEMBANG ANAK - ., Iswarati (PERSATUAN AHLI GIZI INDONESIA, 2010)
FAMILIES’ KNOWLEDGE ON CHILD NURTURING, GROWTH AND DEVELOPMENTHuman capital development in Indonesia is conducted within the framework of an individual’s life cycle, starting from the womb until old age. A child grows and develops under the nurture and care of theparents, therefore parents are the foundation of a child’s personality development. The 2009 Survey on Child Growth and Development was a national survey designed to establish a provincial level estimate. This survey was conducted in Indonesia’s 33 provinces. The goal of the survey was to identify families’ knowledge on how to nurture their children in terms of physical, mental and social development. There were 35,478 people surveyed, with 65.2% living in rural areas and 34.8% were urban population. The majority of respondents were women (80.6%). The research indicates that families’ knowledge in terms of child nurturing were not as expected.The knowledge on how to nurture children from a physical aspect has the highest index score of 66.8, followed by spiritual and social nurturing with an index score of 59.2,and the mental and psychological aspect with an index score of 40.7. The national average of the composite index score was 55.5 with the highest being Central Java province (62) and the lowest being North Maluku (46.3). Better coordination among all related programs is essential in improving efficiency and effectiveness of the programs. Advocacy and socialisation are needed to build public support for the programs.Keywords: family, child nurture, growth and development, national survey